VOCAL HANDICAP AND ASSOCIATION WITH PHYSICAL INACTIVITY AND JOB DISSATISFACTION AMONG TEACHERS - Lilian Souza Melo; Josiane Santos Brant Rocha; Viviana Maia Santos; Leonardo Rodrigues de Souza; Rosângela Ramos Veloso Silva; Desirée Sant´Ana Haikal; Adriane Mesquita Medeiros; Luiza Augusta R. Rossi-Barbosa (PsychTech & Health Journal)
This study aimed to verify the association between voice handicaps, physical inactivity, and job dissatisfaction among public school teachers in Minas Gerais, Brazil. An epidemiological, cross-sectional web survey study was performed to do this. The data compilation relevant to this survey was amassed between October 26 and December 31, 2021. A total of 1782 teachers participated in this study. The outcome variable used was the Voice Handicap Index 10 (VHI-10), which makes it possible to quantify the individual's perception of vocal alteration. The higher the result, the greater the voice handicap perceived by the subject. In addition to sociodemographic and occupational aspects, physical activity was evaluated by the International Physical Activity Questionnaire (IPAQ) in its short form. The level of job satisfaction was expressed through the simple validated question: "Are you satisfied with your job?". The multivariate statistical analysis was Poisson regression with robust variance. Voice handicap was present in 20.2% of the teachers and was associated with being female (PR= 1.32; CI95%:1.03-1.70), teaching time (PR= 1.26; CI95%:1.26-1.04), job dissatisfaction (PR= 1.96; CI95%:1.59-2.42) and physical inactivity (PR= 1.24; CI95%:1.00-1.52). The study was carried out at the beginning of the teachers' return to in-school classes and found that a fifth reported a perception of voice handicap, pointing to the need for greater attention to the work environment and the importance of physical activity for voice health.